2011
DOI: 10.1021/am200500k
|View full text |Cite
|
Sign up to set email alerts
|

Solution Fabrication and Photoelectrical Properties of CuInS2 Nanocrystals on TiO2 Nanorod Array

Abstract: One-dimensional semiconductor architectures are receiving attention in preparing photovoltaic solar cells because of its superior charge transport as well as excellent light-harvesting efficiency. In this study, vertically aligned single-crystalline TiO(2) nanorods array was grown directly on transparent conductive glass (FTO), and then CuInS(2) nanocrystals were deposited on nanorods array by spin coating method to form TiO(2)/CuInS(2) heterostructure films. The resulting nanostructure assembly and compositio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
31
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(32 citation statements)
references
References 40 publications
1
31
0
Order By: Relevance
“…Therefore to enlarge the photoresponse spectrum, considerable efforts have been made, such as doping with transition and/or noble metals [7,8], non-metals [9,10], deposition in quantum dots [11] and construction of heterojunctions with other semiconductors [12][13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore to enlarge the photoresponse spectrum, considerable efforts have been made, such as doping with transition and/or noble metals [7,8], non-metals [9,10], deposition in quantum dots [11] and construction of heterojunctions with other semiconductors [12][13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…A possible explanation is as follows. TiO 2 has no photocatalytic activity in the visible region of λ >420 nm due to its wide band gap (3.6 eV)[15,35]. The ZnIn 2 S 4 with a narrower band gap (2.4eV) allows the photodegradation of methylene blue in visible light region[32].…”
mentioning
confidence: 99%
“…24 A variety of wet and dry methods have been used for deposition of metal sulfide thin films. These methods include chemical bath deposition, 25 spin coating, 26 chemical spray pyrolysis, 27 successive ion layer adsorption and reaction (SILAR), 28 physical vapor deposition (PVD), 29 atomic layer deposition (ALD), 30 modulated flux deposition, 31 electrodeposition 32 and metal-organic chemical vapor deposition (MOCVD) 33 including aerosol assisted chemical vapor deposition (AACVD). 34 It has been found that the thin films deposited by different techniques have different phase structure and degree of crystallinity, thus showing variable electrical as well as optoelectronic properties.…”
Section: Introductionmentioning
confidence: 99%
“…One of the most effective approach is to deposit narrow bandgap semiconductors such as CdS [16][17] , CdSe [18][19] and CuInS 2 [20][21] . However, those semiconductors include toxic or rare elements (Cd, In and Se), which limit the large scale applications.…”
Section: Introductionmentioning
confidence: 99%